ANALISIS MODEL MONETER HARGA FLEKSIBEL DALAM PENENTUAN NILAI TUKAR RUPIAH - Endri, Endri (Universitas Muhammdaiyah Surakarta, 2007)
There are a wide variety of monetary models of exchange rate determination, all of which are outgrowth and extension of the basic flexible-price version pioneered by Frenkel (1978) and Bilson (1978). The research aims to know and prove by empiri-cal means the flexible price monetary model is relevant and advantageous to explain the fluctuation of exchange rate rupiah. The methodology involves testing first two assumption of the monetary model, namely, the price arbitrage (unified goods market) and the existence of a stable money demand function. Having these assumption held, the estimation of fluctuation in exchange rate in 1997-2005 was estimated using the flexible price monetary model developed for this purpose. Estimation of fluctuation in exchange rate suggest that the actual behavior of exchange rate in the period 1997 â 2005 is highly consistent with prediction of the flexible price monetary model. Fluctuation in exchange rate of Indonesia was largely explained by such variables as domestic money demand, domestic income and expected inflation, consistent with hypothesis of the flexible price monetary model.